IoT in Action: Design and Implementation of a Building Evacuation Service - Selahattin Gokceli; Nikolay Zhmurov; Gunes Karabulut Kurt; Berna Ors (Journal of Computer Networks and Communications)
With the development of sensor technologies, various application areas have emerged. The usage of these technologies and exploitation of recent improvements have clear benefits on building applications. Such use-cases can improve smart functions of buildings and can increase the end-user comfort. As a similar notion, building automation systems (BAS) are smart systems that target to provide automated management of various control services and to improve resource usage efficiency. However, buildings generally contain hardware and control services from a diverse set of characteristics. The automated and central management of such functions can be challenging. In order to overcome such issues, an Emergency Evacuation Service is proposed for BAS, where requirements of such central management model are analyzed and model content and subservice definitions are prepared. A crucial scenario, which could be a necessity for future BAS, is defined and an approach for evacuation of people in the buildings at emergency situations is proposed. For real-life scenarios, the Evacuation Service is implemented by using a low-cost design, which is appropriate for Internet of Things (IoT) based BAS applications. As demonstrated, the proposed service model can provide effective performance in real-life deployments.